“Milky Way Astronomies”: Proposing a Framework for Cultural Comparison - Lopez, Alejandro Martin (2022)
The Milky Way is a feature of the night sky that has had cosmological significance in many cultures around the world at different times. Many works, especially in South America and Australia, have drawn attention to the fact that in some cultures the bright band of our galaxy has a structural role; others have pointed out the importance of the “dark constellations” outlined against its bright background. Some researchers have revealed regional similarities in reference to this bright region, and others have analysed the world occurrence of these so-called “dark constellations”. In this contribution, based on the experience of all these previous works, I want to go one step further, proposing a general framework for a more fruitful comparison. I propose considering the broad spectrum of features related to this bright band and its dark spots in their relations and connections. Seen in this way it is possible to make a “middle-range” model, a polythetic class, that I propose to call “Milky Way astronomies”. This would characterise some astronomies in the world, in which an articulated set of features linked to our galaxy has a key role, and can serve as a heuristic tool that allows us to delve into the meaning of each of these systems and their logic, studying in a systematic way not only the similarities between them but also the differences.